Pengaruh kitosan terhadap peningkatan level ekspresi WRKY17 dan WRKY53 tanaman Capsicum annuum cv. Laba pada kondisi kekeringan - Muhammad Abdul AZIZ; Rizkita Rahmi ESYANTI; Fenny Martha DWIVANNY (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2020)
Chitosan is known as the natural plant growth biostimulant and defense elicitor involving WRKY transcription factors in response to environmental stresses. However, either plant’s growth or defense responses against stress are different among the cultivars. In the previous study, chitosan and drought treatment combination on red chili plant cv. Lado resulted in the impeded growth performance followed by the down-regulated expression level of WRKY17. Hence, this study aimed to investigate the response of red chili plant from the different cultivar towards the combination of chitosan and drought treatments. At the onset of the generative phase, plants were subjected to the drought treatment with and without 1 mg mL-1 of chitosan application. Observation of plant growth performance was carried out by measuring plant height, the number of leaves, the conversion percentage of flowers developed to fruits, and the number of harvested fruits, while the molecular parameter was indicated by the analyses of WRKY17 and WRKY53 expression levels. In line with the previous study using cv. Lado, the combination of 1 mg mL-1 of chitosan and drought treatment significantly reduced the plant productivity observed in the number of fruits, followed by the plant height and the number of leaves. However, the expression level of WRKY17 and WRKY53 experienced 10 and 22-fold higher than controls, respectively. This is different from the previous study which showed the reduction of WRKY17 expression level. According to the study, it can be implied that the combination of chitosan and drought treatments on red chili plant cv. Laba could reduce plant growth performance, but increased genetics indicator towards plant’s defense system against stress indicated by the escalation of WRKY17 and WRKY53 expression level. Furthermore, the individual chitosan application are potential to increase the productivity of red chili plant cv. Laba.